Information systems in environmental risk management - Inđić, Dejan; Terzić, Miroslav R.; Ivanković, Negovan D. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Abstract: Earthquakes, floods, nuclear and chemical accidents, air pollution, soil and water, indicating the increasing presence of accidents caused by intensive development and often uncontrolled application of technological development. Before the company raises the problem of how to better prepare, how to ensure greater compatibility and operation activities and measures for the prevention of accidents and to make changes in the social and technological developments that will go in favor of nature, but also for the benefit of future generations. The paper describes the use of various information systems (IS) in the management of environmental risks and the proposal to develop a unique IS in Serbia.